Validation of the advance care planning engagement survey in Singapore - Gwendoline Wan Hua Tan; Ginny Si Min Quek; Nathaniel Jun Xian Lum; Lian Leng Low; Yu Xian Loo (BMC Palliative Care)
Abstract Background Singapore has an ageing population. End-of-life care and advance care planning are becoming increasingly important. To assess advance care planning engagement, valid tools are required. The primary objective of the study is to validate the 15-, 9- and 4-item versions of the ACP Engagement Survey in Singapore. Methods 10 inpatients in a Singapore community hospital were purposively sampled for a cognitive debriefing interview on the ACP Engagement Survey. We recruited patients 21 years and older, who were able to understand and speak English, without a diagnosis of dementia, and who were not admitted under the palliative care service. Next, 150 inpatients and caregivers were recruited using convenience sampling across 2 Singapore community hospitals to complete the 15-item ACP Engagement Survey. We assessed content validity, internal consistency with Cronbach’s alpha, construct validity with hypotheses testing and test-retest reliability using intraclass correlation coefficients. Results The ACPES scores were significantly higher for those who reported yes for pre-planning activities such as making a will, making a lasting power of attorney, telling one’s doctor about end-of-life care preferences, and telling family or loved ones about end-of-life care preferences. Cronbach’s alpha was 0.945 for the 15-item version, 0.915 for the 9-item version, and 0.912 for the 4-item version. Intraclass correlation coefficient was 0.933 for the 15-item version, 0.938 for the 9-item version and 0.865 for the 4-item version. Conclusions This study provided good psychometric support for the validity of the 15-item, 9-item and 4-item versions of the ACP Engagement Survey in Singapore. Trial registration SingHealth Centralised Institutional Review Board (CIRB) approved this study (reference 2022/2025).